2023
DOI: 10.1007/s11119-023-10083-z
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting carrot yield with optimal timing of Sentinel 2 image acquisition

L. A. Suarez,
M. Robertson-Dean,
J. Brinkhoff
et al.

Abstract: Accurate, non-destructive forecasting of carrot yield is difficult due to its subterranean growing habit. Furthermore, the timing of forecasting usually occurs when the crop is mature, limiting the opportunity to implement alternative management decisions to improve yield (during the growing season). This study aims to improve the accuracy of carrot yield forecasting by exploring time series and multivariate approaches. Using Sentinel-2 satellite imagery in three Australian vegetable regions, we established a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Root sampling consisted of two data collection periods: 82 and 116 DAS, with 50 points at each data collection in both experimental areas (total: 200 sampling points). These periods were chosen according to the best time for crop modeling according to Suarez et al [13], corresponding to the full radial filling (82 DAS) and the date before crop harvesting (116 DAS). The climatic conditions were 1600 degree-days and 2260 degree-days (base temperature of 3 • C) for 82 and 116 DAS, respectively (Figure 2).…”
Section: Root Sampling and Biometric Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Root sampling consisted of two data collection periods: 82 and 116 DAS, with 50 points at each data collection in both experimental areas (total: 200 sampling points). These periods were chosen according to the best time for crop modeling according to Suarez et al [13], corresponding to the full radial filling (82 DAS) and the date before crop harvesting (116 DAS). The climatic conditions were 1600 degree-days and 2260 degree-days (base temperature of 3 • C) for 82 and 116 DAS, respectively (Figure 2).…”
Section: Root Sampling and Biometric Assessmentmentioning
confidence: 99%
“…Different predictive approaches to crop parameters leveraging remote sensing (RS) and artificial intelligence (AI) are being explored in the literature [11][12][13]. RS involves collecting data on the Earth's surface using sensors installed on satellites or remotely piloted aircraft to monitor large areas at low costs [14], control in-season weeds, identify the health of the crop, and predict crop yield in a non-destructive way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schauberger et al [19] reported the extent of studies on the yield forecasting of horticultural crops, while studies by Suarez et al [20,21] described the importance of carrot yield forecasting and explored satellite images used for carrot yield prediction. Wei [22] generated carrot yield maps using planetScope hyperspectral data with a high accuracy (R 2 = 0.68-0.82), and a study by de Lima Silva [23] achieved a good carrot predicted yield accuracy (R 2 = 0.68) using planetScope CubeSat Platform.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36]. Examples include sunflower [37], sugarcane [38], rice [39], corn [40], wheat [41], carrot [20][21][22], etc. The ML algorithms, including neural network (NN), stacked autoencoder (SAE), recurrent NN (RNN), graph NN (GNN), and restricted Boltzmann machine (RBM), have been widely used in agricultural applications [32].…”
Section: Introductionmentioning
confidence: 99%